2022
DOI: 10.1097/bs9.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Mature plasmacytoid dendritic cells associated with acute myeloid leukemia show similar genetic mutations and expression profiles to leukemia cells

Abstract: Introduction:Mature plasmacytoid dendritic cells (pDCs) proliferation associated with myeloid neoplasms (MPDMN) are recognized as a neoplasm related to fully differentiated pDCs. Although it has been reported for many years, the genomic landscape of MPDMN is poorly understood.Methods:We reported two patients who developed acute myeloid leukemia (French-American-British M5 subtype) coexisted with immunophenotypically mature pDCs proliferation, which fit the diagnosis of MPDMN. We sorted pDCs from myeloid blasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Thus, two subsets of pDC-AML can be suggested, pDC-M0-AML and secondary monocytic pDC-AML [ 102 , 103 ]. Recently, such results were also confirmed in two cases of monocytic pDC-AML, bearing RUNX1 and FLT3-ITD mutations in blast cells and in pDCs [ 113 ].…”
Section: Genetics Of Pdc Proliferation Associated With a Myeloid Diso...mentioning
confidence: 66%
“…Thus, two subsets of pDC-AML can be suggested, pDC-M0-AML and secondary monocytic pDC-AML [ 102 , 103 ]. Recently, such results were also confirmed in two cases of monocytic pDC-AML, bearing RUNX1 and FLT3-ITD mutations in blast cells and in pDCs [ 113 ].…”
Section: Genetics Of Pdc Proliferation Associated With a Myeloid Diso...mentioning
confidence: 66%
“…It is unclear whether mature pDC proliferation in tissue and bone marrow in the context of AML are the same neoplastic process as those in pDC-AML. Reports have shown that pDCs in MPDCP associated with AML had genetic mutations and expression profiles similar to those in the associated AML blasts, including pathogenic RUNX1 and FLT3-ITD mutations [11]. The following table summarizes reported cases where pDCs were increased in bone marrow with a concurrent diagnosis of AML.…”
Section: Plasmacytoid Dendritic Cell Development and Summary Of Repor...mentioning
confidence: 99%